IMPLEMENTASI PROGRAM DAGUSIBU MELALUI PENDEKATAN LEAFLET DALAM MENINGKATKAN PENGETAHUAN MASYARAKAT KELURAHAN WATU-WATU TENTANG AKSES DAN PEROLEHAN OBAT YANG TEPAT - Asniar Pascayantri; Adryan Fristiohady; Irnawati Irnawati; Asriullah Jabbar; Sabarudin Sabarudin; Hasnawati Hasnawati; Nur Illyin; Astrid Indalifiany; Fadhliyah Malik; Vica Aspadiah; Rahmat Mualiadi; Dian Munasari Solo; La Ode Muhammad Fitrawan; Nasrudin Nasrudin; Ari sartinah; Muhammad Ilyas Y; Mubarak Mubarak (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
Low drug literacy can lead to drug misuse, irrational self-medication, and the procurement of medicines from unofficial sources. This community service activity aimed to improve the knowledge of Watu-Watu Village residents on proper drug access and acquisition through the DAGUSIBU program, using educational leaflets, discussions, and interactive question-and-answer sessions. Program effectiveness was measured using pre- and post-tests, as well as Likert-scale evaluations. Results showed an increase in community knowledge from 61% to 100%, and the program received a mean evaluation score of 4.83 out of 5. The leaflet-based DAGUSIBU program, combined with active interaction, effectively improved community drug literacy and can serve as a replicable model for community-based pharmaceutical education.